Nation-building through NHDP - Lal, A.K. (2003)
Infrastructure development has been the prime mover of the national economy in many of the developed countries. In recent years, in India too, there has been growing thrust on improving infrastructure capabilities in road, power and communication sectors. Prime Minister's prestigious National Highway Development Project (NHDP) is a example of how need for an efficient and modern transportation has received greater attention from the Union Government for putting the nation on fast - track to prosperity. - Reproduced.
Keywords: Nation building; Infrastructure development